Exploring college-student insights on learning aids and practicum equipment - The, Hery Yanto; Sujata, Dian Tika (Universitas Negeri Yogyakarta, 2025)
Reflecting on the use of learning media will help students decide on a quality and user-friendly design. Thus, this study examines the experiences of second-year students in the Buddhist Religious Education program at Institut Nalanda who participated in the online distance